Effect of Oxygen Concentration in Inert Gas Environments on Friction and Wear of Carbon Nitride Coatings - Pengfei Wang (Japanese Society of Tribologists, 2011)
A systematic analysis of the effect of oxygen concentration in inert gas environments on friction and wear properties of carbon nitride (CNx) coatings is discussed in this paper. The friction tests in inert gas environments with constant and increasing oxygen concentration were performed using a ball-on-disk tribometer equipped with a gas blow unit and a ball-on-disk tribometer situated inside a steel chamber, respectively. It is found that the friction coefficients of CNx coatings in inert gas environments increased linearly from 0.04 or less to around 0.10 with the increase of oxygen concentration from 0 to 10 vol.%. Their increased slowly to 0.12 with further increasing oxygen concentration. The specific wear rates of the ball and the disk in the range of friction coefficients less than 0.06 were in the order of 10-8 mm3/Nm and 10-7 mm3/Nm, respectively. These wear rates increased almost linearly with the increase of oxygen concentration in inert gas environments, except for the case of CNx coated Si3N4 ball. The friction and wear mechanisms of CNx coatings in inert gas environments with different oxygen concentration were discussed according to the composition and structural changes of worn surfaces on disks by using XPS and Raman analysis.